Validity of biomarkers in screening for neonatal sepsis - A single center -hospital based study - Nagwan I. Rashwan; Mohammed H. Hassan; Zeinab M. Mohey El-Deen; Ahmed El-Abd Ahmed (Elsevier, 2019)
Background: The diagnosis of neonatal sepsis still considered to be a challenge for both clinicians and the laboratory due to the non-specific clinical presentations. The present study aimed to compare and assess the diagnostic & prognostic values of C-reactive protein (CRP), high sensitivity CRP (hsCRP), presepsin, interleukin-6 (IL-6) and procalcitonin (PCT) in neonatal sepsis separately and in combination. Methods: This hospital-based cross-sectional study has been conducted on 168 neonates recruited from the neonatal intensive care unit (NICU) of Qena University Hospitals, Upper Egypt. Measurements of CRP using latex agglutination test, hsCRP, presepsin, IL6 and PCT assays using commercially available ELISA assay kits were done to all included neonates. Results: There were significantly higher serum levels of CRP among late onset versus early onset sepsis group with significantly higher serum levels of hsCRP and presepsin among early onset compared with the late onset sepsis group (p < 0.05 for all). There were significantly higher hsCRP, presepsin and PCT serum levels in proven versus probable sepsis group (p < 0.05 for all). Significantly higher serum levels of presepsin and PCT were noted among survivors versus non survivors sepsis group (p < 0.05 for all). The cutoff value of the serum level of CRP >6 mg/dl showed lower sensitivity and specificity than that of hsCRP at cutoff >140 ng/ml in diagnosing neonatal sepsis. The cutoff value of presepsin >200 ng/ml showed equal sensitivity and specificity to IL-6 at cutoff >22 pg/ml. The cutoff value of PCT at > 389 pg/ml showed sensitivity and specificity approximate to that of hsCRP. Conclusions: CRP could be a helpful prognostic marker in late onset neonatal sepsis. hsCRP and PCT have higher diagnostic accuracy in neonatal sepsis in comparison to other studied markers. Both IL-6 and presepsin have equal diagnostic utility in neonatal sepsis, but presepsin could be helpful diagnostic marker in early onset neonatal sepsis. Key Words: high sensitivity CRP, interleukin-6, neonatal sepsis, presepsin, procalcitonin